TALABALARNING HUQUQIY KOMPETENTLIGINI RIVOJLANTIRISH – DOLZARB PEDAGOGIK MUAMMO SIFATIDA - Tilewov, E. (SCIENCE and SOCIETY, 2023)
Achieving the supremacy of laws in society ensures that every social relationship is regulated on the basis of the principle of justice. The article revealed the need for students to be able to demonstrate not only thorough mastery of professional theoretical and practical knowledge, but also the ability to apply them in professional activity without any difficulty, on the basis of legal competence.